A novel strategy for bioactive natural products targeting NLRP3 inflammasome in Alzheimer’s disease - Yang, Zhiyou; Liu, Junxin; Wei, Shuai; Deng, Jiahang; Feng, Xinyue; Liu, Shucheng; Liu, Mingxin (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD), the most common type of dementia, is an ageing-related progressive neurodegenerative brain disorder. Extracellular neuritic plaques composed of misfolded amyloid β (Aβ) proteins and intracellular neurofibrillary tangles formed by hyperphosphorylated tau protein are the two classical characteristics of AD. Aβ and tau pathologies induce neurite atrophy and neuronal apoptosis, leading to cognitive, language, and behavioral deficits. For decades, researchers have made great efforts to explore the pathogens and therapeutics of AD; however, its intrinsic mechanism remains unclear and there are still no well-established strategies to restore or even prevent this disease. Therefore, it would be beneficial for the establishment of novel therapeutic strategy to determine the intrinsic molecular mechanism that is interrelated with the initiation and progression of AD. A variety of evidence indicates that neuroinflammation plays a crucial role in the pathogenesis of AD. Nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain-containing protein 3 (NLRP3) is a key inflammasome sensor of cellular stress and infection that is involved in the innate immune system. In response to a wide range of stimuli like Aβ, NLRP3 assembles apoptosis-associated speck-like protein (ASC) and procaspase-1 into an inflammasome complex to induce the caspase-1 mediated secretion of interleukin (IL)-1β/IL-18 in M1 polarized microglia, triggering the pathophysiological changes and cognitive decline of AD. Therefore, targeting NLRP3 inflammasome seems an efficient path for AD treatment via regulating brain immune microenvironment. Furthermore, accumulating evidence indicates that traditional Chinese medicine (TCM) exerts beneficial effects on AD via NLRP3 inflammasome inactivation. In this review, we summarize current reports on the role and activated mechanisms of the NLRP3 inflammasome in the pathogenesis of AD. We also review the natural products for attenuating neuroinflammation by targeting NLRP3 inflammasome activation, which provides useful clues for developing novel AD treatments.